A Bi‐Layer Hydrogel Cardiac Patch Made of Recombinant Functional Proteins. Issue 19 (3rd April 2022) - Jiang, Xiaoyu; Feng, Teng; An, Bolin; Ren, Susu; Meng, Jufeng; Li, Ke; Liu, Suying; Wu, Haiying; Zhang, Hui; Zhong, Chao
Abstract: The development of minimally invasive cardiac patches, either as hemostatic dressing or treating myocardial infarction, is of clinical significance but remains a major challenge. Designing such patches often requires simultaneous consideration of several material attributes, including bioabsorption, non‐toxicity, matching the mechanic properties of heart tissues, and working efficiently in wet and dynamic environments. Using genetically engineered multi‐domain proteins, a printed bi‐layer proteinaceous hydrogel patch for heart failure treatments is reported. The intrinsic self‐healing nature of hydrogel materials physically enables seamless interfacial integration of two disparate hydrogel layers and functionally endows the cardiac patches with the combinatorial advantages of each layer. Leveraging the biocompatibility, structural stability, and tunable drug release properties of the bi‐layer hydrogel, promising effects of hemostasis, fibrosis reduction, and heart function recovery on mice is demonstrated with two myocardium damage models. Moreover, this proteinaceous patch is proved biodegradable in vivo without any additive inflammations. In conclusion, this work introduces a promising new type of minimally invasive patch based on genetically modified double‐layer protein gel for treating heart‐related injuries or diseases. Abstract : A new type of minimally invasive cardiac patch based on 3D printed, genetically modified double‐layer protein gel is developed. The biocompatible and biodegradable hydrogel patch exhibits promising effects of hemostasis, fibrosis reduction, and heart function recovery on mice with two myocardium damage models.